Aprendizagem baseada em problemas aplicada ao ensino de direito: Projeto exploratório na área de relações de consumo - Carlini, Angélica Luciá (2006)
The work contemplates the experience accomplished with the application of the paradigm of learning based on problems, in two groups of Law School undergraduation students, in the period between June 2004 and June 2005, in the São Francisco University, in Bragança Paulista, concerning the study of consumption relations and the consumer's right. The experience was carried out aiming at answering to the query whether the paradigm of learning based on problems is possible of being used in teaching Law in Brazil and, whether this paradigm can mean a renewal in the teaching-learning relation both for teachers and for Law students. The methodological option used was that of qualitative research. The accomplished research comprised the bibliographical-research and the action-research and the used procedures were the participant-observation and the non-directive interview. The research rebuilds the historical path of the Law courses in Brazil, with the objective of drawing a backdrop for the reflection over the need of changes in the teaching-learning relation, which nowadays is still marked, in those courses, by little stimulating practices, like the prevailing use of the traditional expository class pattern, understood as the one where the teacher is the knowledge transmitter for the students who passively receive it. Besides, the Law teaching is also marked by an excessive attachment to the positivism, what results in the lack of room for the construction of a critical reflection about the Law science. The study analyzes the theoretical bases on which the paradigm of learning based on problems is built, and its possibility of being applied to the Law teaching in Brazil. The research discusses the relevant aspects of the developed experience, especially the problems built and introduced to the students, discussing the ways they have built the solutions. Moreover, it analyzes the students' performance in field works, with adolescents and tradesmen of Bragança Paulista, moment in which they taught to lay people relevant aspects of the consumer's right and of consumption relations